Is longer education a substitute for job search through social contacts? - Dagmar Müller (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2021)
This paper investigates whether longer upper secondary education affects the role of parents in the job finding process. Previous research has shown that less educated workers rely more on contacts, and theory suggests that education and social connections can be substituted as signals of ability. I investigate this question by exploiting a Swedish trial that generated exogenous variation across municipalities and student cohorts in the length of vocational upper secondary education. Relying on Swedish matched employer-employee data, I estimate the effect of receiving one more year of education on the probability of being employed at the same establishment as a parent for up to 20 years after graduation. The results indicate that the average impact of a longer education is negative during the early career and non-trivial in magnitude. The overall effect is entirely driven by a large and statistically significant effect within the group of vocational students with high-educated parents. For the group of students where the use of parental ties is most prevalent, students with low-educated parents, the reliance on parental contacts appears resilient to policy-induced changes in the length of education.
Keywords: J62; J24; 330; social contacts; young workers; labor market transitions; mobility